THE DETERMINATION OF CULTURAL LANDSCAPE VALUES OF BILECIK CITY - GÖKER, Parisa; ERDOĞAN, Elmas (EUROASIA JOURNAL OF SOCIAL SCIENCES & HUMANITIES, 2019)
Cultural landscapes can be defined as landscapes with unique qualities formed by full or partial transformation of the natural landscape as a result of human intervention within the historical process. Cultural landscapes can be explained as the areas that are subject to settlements and changed throughout time by the contribution of mankind and also is a system, including both natural and physical factors emerging based on human activities. In addition to its historical character, it also reflects the natural values of the past as well as the artistic characteristics and life style of the respective area of the present. Furthermore, using the cultural landscape values for tourism intended activities contributes to the local development. However, it is a must to ensure the protection and sustainability of cultural landscape values. As being one of the smallest and least-populated cities of Turkey, Bilecik has witnessed an important role for many civilization due to its strategic location as well as its status as the first capital of the Ottoman Empire. Besides the city has a crucial role in the Declaration of the Republic of Turkey with its struggle and victories gained in the Independence War of Turkey. Therefore, there are many archeological and historical artifacts within the borders of this province as an old settlement area bearing the traces of various civilizations from ancient ages to the present time. The main objective of this research is to determine the cultural landscape values of Bilecik city and its near environs which is rich in cultural landscapes. In this context, the spatial characteristics, recreational usage opportunities and cultural values in terms of historical, archeological and local architectural values of the city will be examined thoroughly with SWOT analysis. The places and areas that contribute the cultural landscape of the study area will be determined in line with the obtained data, then they will be processed onto the area map for Bilecik province. Finally, suggestions will be developed for the preservation of cultural landscape values for the sustainability of the heritage areas